Os 30 years of state constitutions in Brazil and the state fundamental rights - Sgarbossa, Luís Fernando (2019)
State constitutionalism is a relevant theme and, however, still little studied in Brazil. Several issues related to the state constitutionalism claim for studies, such as the state fundamental rights, object of the present paper. The article is a partial result of basic research on the nature and quantitative / qualitative approach, as well as documentary, survey and bibliographic, on procedures, besides using the structural-comparative, technical-comparativeand descriptive-comparative methods. After a brief introduction, the paper provides a comparative overview of the Brazilian state constitutions in several aspects, such as the extension, content and stability of these charters. After, it outlines general aspects relatedto Brazilian constitutional pluralism, understood as the situationof coexistence of general and partial constitutional orders, withrespect to fundamental rights and guarantees, evidencing thepresence of state rights and guarantees beyond the federal ones.Finally, it analyzes some of the existing state fundamental rights andrelated issues, notably the opening clause existing in various stateconstitutions, which connects the state and the federal constitutionalorders and, eventually, also the supranational legal order; examinesthe theme of state fundamental rights wholly or partially coincidentwith analogous federal rights, and finally examines the theme ofautonomous or specific state fundamental rights, thus understoodas those that do not fully or partially coincide with the fundamentalrights provided for in the federal constitutional order